Effect of Debris Flows post the 2010 eruption of mount Merapi on Environment and Socio-Economic Condition in Progo River and Its Tributaries - Jazaul Ikhsan, Puji harsanto, Muhammad Sulaiman (Fakultas Teknik UGM, 2013)
the study aims to investigate morphological condition, damage due to debris flow and its impact on inhabitant life as well as environmental change.